Nonlinear analysis of axial-compressed corroded circular steel pipes reinforced by FRP-casing grouting. (February 2023) - Fu, Hao; Zhang, Jiayi; Wu, Zhaoqi; Chin, Chee-Loong; Ma, Chau-Khun
Abstract: In this paper, ABAQUS software is used to carry out finite element simulation on the axial compression performance of corroded round steel pipe members reinforced by FRP casing grouting. Moreover, its working mechanism and failure mode are analyzed. A typical load-displacement curve of the component is obtained. Furthermore, the effect of FRP pipe thickness, grouting thickness, corrosion rate, concrete strength, and slenderness ratio on the mechanical performance of the component is explored. The research results indicate that the component load-displacement curve can be characterized by bilinear and trilinear models. The former corresponds to the overall buckling failure mode, while the latter corresponds to the strength failure mode for the bare ends of a round steel tube. After reinforcement, the component bearing capacity increases up to 166.83%. Moreover, the increase is positively correlated with FRP pipe thickness, grouting thickness, and corrosion rate. The component bearing capacity first decreases and then increases when modifying the slenderness ratio, while concrete strength has a minor effect on it. Moreover, the bending stiffness ratio equation and the stability bearing capacity correction equation of the axial compression reinforced components are proposed. The aforementioned provides reference suggestions for practical engineering applications of corroded steel structures reinforced by FRP casing grouting. Highlights: Adopt FRP casing grouting method to increase the component bearing capacity of corroded round steel pipe up to 166.83%. The axial-compressed reinforcement component can be classified as a bilinear model component and a trilinear model component. The existence of the bound bending stiffness ratio is found in the parameterization simulation. Adopt the conversion section method to derive the bearing capacity calculation formula and make corrections.